2004
DOI: 10.1529/biophysj.103.034876
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Heme Iron-Lipid Acyl Chain Coordination in Escherichia coli Flavohemoglobin

Abstract: Escherichia coli flavohemoglobin is endowed with the notable property of binding specifically unsaturated and/or cyclopropanated fatty acids both as free acids or incorporated into a phospholipid molecule. Unsaturated or cyclopropanated fatty acid binding to the ferric heme results in a spectral change observed in the visible absorption, resonance Raman, extended x-ray absorption fine spectroscopy (EXAFS), and x-ray absorption near edge spectroscopy (XANES) spectra. Resonance Raman spectra, measured on the fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 41 publications
(52 reference statements)
0
35
0
Order By: Relevance
“…In agreement with the crystallographic data, optical absorption (both in solution and in crystals) and resonance Raman spectroscopy point out unambiguously that the lipid-free ferric derivative is a pentacoordinate species, and the Leu57(E11) residue does not establish a bonding interaction with the ferric iron. In contrast, the formation of a hexacoordinate derivative is clearly demonstrated upon lipid binding to the ferric HMP protein by the low frequency shift of the core size marker bands (22). The appearance of a hexacoordinate high spin species is accompanied by an unusually intense band at (23).…”
Section: Lipid-binding Propertiesmentioning
confidence: 96%
“…In agreement with the crystallographic data, optical absorption (both in solution and in crystals) and resonance Raman spectroscopy point out unambiguously that the lipid-free ferric derivative is a pentacoordinate species, and the Leu57(E11) residue does not establish a bonding interaction with the ferric iron. In contrast, the formation of a hexacoordinate derivative is clearly demonstrated upon lipid binding to the ferric HMP protein by the low frequency shift of the core size marker bands (22). The appearance of a hexacoordinate high spin species is accompanied by an unusually intense band at (23).…”
Section: Lipid-binding Propertiesmentioning
confidence: 96%
“…coli FHb is inactive toward peroxidase substrates, and the ferric FHb does not react with H 2 O 2 . However, the latter binds unsaturated or cyclopropanated fatty acids and acts as an alkylhydroperoxide reductase with NADH as electron donor, catalyzing the reduction of alkylhydroperoxides to the corresponding alcohols (30). These results suggest that FHb may be involved in the repair of oxidatively damaged lipid membranes.…”
Section: Peroxidase Activity and Reaction With Free Radicalsmentioning
confidence: 95%
“…An accurate structural characterization has been obtained on metal ionic solutions [12], different heme models and heme containing proteins [13][14][15], showing that a combined analysis of the EXAFS and XANES regions of the spectrum is able to provide unambiguous details on the local structure in solution around the metal center.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Previous investigations have shown that for a quantitative EXAFS analysis of hemeproteins MS fourbody terms have to be accounted for [13][14][15][16]20]. The inclusion of these higher order contributions is essential to obtain a good agreement between theoretical and experimental data.…”
Section: Exafs Data Analysismentioning
confidence: 99%
See 1 more Smart Citation